Comprehensive Profiling of Tubby-Like Proteins in Soybean and Roles of the GmTLP8 Gene in Abiotic Stress Responses - Xu, Hong-Ru; Liu, Ying; Yu, Tai-Fei; Hou, Ze-Hao; Zheng, Jia-Cheng; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Fu, Jin-Dong; Ma, You-Zhi; Wei, Wen-Liang; Xu, Zhao-Shi (Frontiers in Plant Science, 2022)
Tubby-like proteins (TLPs) are transcription factors that are widely present in eukaryotes and generally participate in growth and developmental processes. Using genome databases, a total of 22 putative TLP genes were identified in the soybean genome, and unevenly distributed across 13 chromosomes. Phylogenetic analysis demonstrated that the predicted GmTLP proteins were divided into five groups (I-V). Gene structure, protein motifs, and conserved domains were analyzed to identify differences and common features among the GmTLPs. A three-dimensional protein model was built to show the typical structure of TLPs. Analysis of publicly-available gene expression data showed that GmTLP genes were differentially expressed in response to abiotic stresses. Based on those data, GmTLP8 was selected to further explore the role of TLPs in soybean drought and salt stress responses. GmTLP8 overexpressors had improved tolerance to drought and salt stresses, whereas the opposite was true of GmTLP8-RNAi lines. DAB and NBT staining and physiological indexes also showed that overexpression of GmTLP8 enhanced the tolerance of soybean to drought and salt stresses; in addition, downstream stress-responsive genes were upregulated in response to drought and salt stresses. This study provides new insights into the function of GmTLPs in response to abiotic stresses.